Adaptive micro-credential-based curriculum to address competency gaps and industry needs - M. Fatih Hidayatul Mustafid; Nadlir Nadlir (Inovasi Kurikulum, 2026)
Digital transformation has rapidly changed the competency needs of the workforce, creating a gap between the competencies of university graduates and industry demands. This situation demands the development of a curriculum that is more adaptive, flexible, and oriented to job market needs. This study aims to analyze the role of a micro-credential-based adaptive curriculum in reducing the competency gap and increasing graduates' relevance in the era of digital transformation. This study employs a systematic literature review to examine references on digital transformation, adaptive curriculum, and the implementation of micro-credential in higher education. The results of the study indicate that micro-credential can provide recognition of specific competencies needed by industry, support flexible and continuous learning, and improve graduates' work readiness through mastery of technical and non-technical skills. The integration of micro-credential into the curriculum strengthens the connection between the learning process and the dynamic needs of the workforce. However, its implementation still faces challenges, including standardization of certification, industry recognition of competencies, human resource readiness, and digital infrastructure support. These findings confirm that a micro-credential-based adaptive curriculum is an innovative strategy for improving graduate quality and the competitiveness of higher education in the digital era.   Abstrak Transformasi digital telah dengan cepat mengubah kebutuhan kompetensi tenaga kerja, sehingga memunculkan kesenjangan antara kompetensi lulusan perguruan tinggi dan tuntutan dunia industri. Kondisi ini menuntut pengembangan kurikulum yang lebih adaptif, fleksibel, dan berorientasi pada kebutuhan pasar kerja. Penelitian ini bertujuan untuk menganalisis peran kurikulum adaptif berbasis micro-credential dalam mengurangi kesenjangan kompetensi sekaligus meningkatkan relevansi lulusan di era transformasi digital. Penelitian ini menggunakan metode systematic literature review dengan menelaah berbagai referensi yang berkaitan dengan transformasi digital, kurikulum adaptif, serta implementasi micro-credential dalam pendidikan tinggi. Hasil kajian menunjukkan bahwa micro-credential mampu memberikan pengakuan terhadap kompetensi spesifik yang dibutuhkan industri, mendukung pembelajaran yang fleksibel dan berkelanjutan, serta meningkatkan kesiapan kerja lulusan melalui penguasaan keterampilan teknis maupun nonteknis. Integrasi micro-credential dalam kurikulum memperkuat keterhubungan antara proses pembelajaran dan dinamika kebutuhan dunia kerja. Namun, implementasinya masih menghadapi tantangan berupa standardisasi sertifikasi, pengakuan kompetensi oleh industri, kesiapan sumber daya manusia, serta dukungan infrastruktur digital. Temuan ini menegaskan bahwa kurikulum adaptif berbasis micro-credential merupakan strategi inovatif untuk meningkatkan kualitas lulusan dan daya saing pendidikan tinggi di era digital. Kata Kunci: kesenjangan kompetensi; kurikulum adaptif; micro-credential